The role of genomics in transfusion medicine. Issue 6 (November 2018) - Wheeler, Marsha M.; Johnsen, Jill M.
Abstract : Purpose of review: To summarize recent advances in red blood cell (RBC) blood group genotyping, with an emphasis on advances in the use of NGS next generation sequencing (NGS) to detect clinically relevant blood group gene variation. Recent findings: Genetic information is useful in predicting RBC blood group antigen expression in several clinical contexts, particularly, for patients at high-risk for allosensitization, such as multiple transfused patients. Blood group antigen expression is directed by DNA variants affecting multiply genes. With over 300 known antigens, NGS offers the attractive prospect of comprehensive blood group genotyping. Recent studies from several groups show that NGS reliably detects blood group gene single nucleotide variants (SNVs) with good correlation with other genetic methods and serology. Additionally, new custom NGS methods accurately detect complex DNA variants, including hybrid RH alleles. Thus, recent work shows that NGS detects known and novel blood group gene variants in patients, solves challenging clinical cases, and detects relevant blood group variation in donors. Summary: New work shows that NGS is particularly robust in identifying SNVs in blood group genes, whereas custom genomic tools can be used to identify known and novel complex structural variants, including in the RH system.